1992
DOI: 10.1007/bf02253592
|View full text |Cite
|
Sign up to set email alerts
|

The McCollough effect as a measure of central cholinergic activity in man

Abstract: The McCollough Effect (ME) is an orientation contingent colour after-effect which has been proposed as an indicator of central neurotransmitter activity. Shute (1979) suggested that the ME could reflect a hippocampal "forgetting" mechanism which should be inhibited by GABAergic neurones and stimulated by cholinergic neurones. The purpose of the present study was to demonstrate that the ME is in fact sensitive to cholinergic and anticholinergic drugs and to compare its sensitivity to more conventional tests of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…He suggested that the initial strength of the ME varied inversely with levels of cholinergic activity and supported this with a number of'uncontrolled exploratory observations. We have verified this in a number of drug studies with normal male subjects: ME strength is depressed by cholinergic agonists (physostigmine) and elevated by antagonists (hyoscine) (Byth et al, 1992;McMahon, 1993). However, initial strength is also reduced by caffeine Shute, 1979) and nicotine (Amure, 1978), which do not exert their actions primarily through the cholinergic system, although ACh may be involved.…”
Section: Andsupporting
confidence: 53%
See 4 more Smart Citations
“…He suggested that the initial strength of the ME varied inversely with levels of cholinergic activity and supported this with a number of'uncontrolled exploratory observations. We have verified this in a number of drug studies with normal male subjects: ME strength is depressed by cholinergic agonists (physostigmine) and elevated by antagonists (hyoscine) (Byth et al, 1992;McMahon, 1993). However, initial strength is also reduced by caffeine Shute, 1979) and nicotine (Amure, 1978), which do not exert their actions primarily through the cholinergic system, although ACh may be involved.…”
Section: Andsupporting
confidence: 53%
“…In the beginning of this paper, we offered two competing predictions of the way in which the ME might vary across the menstrual cycle. Since we had previously shown that the ME is sensitive to cholinergic activity (Byth et al, 1992), we suggested that the ME would be strongest in the first part of the cycle when rising estrogen levels reduce cholinergic activity. Alternatively, ifthe ME should be affected inversely by CNS arousal, ME strength would be greatest in the second part of the cycle when rising progesterone levels have a deactivating effect, reducing arousal.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations